Pemberdayaan Masyarakat Melalui Potensi Lokal Sukun dalam Upaya Mendukung Pengembangan Pariwisata Berkelanjutan di Negeri Latuhalat, Kota Ambon - Simona C.H. Litaay; Hermien L. Soselisa; Elsina Titaley; Syane Matatula; Christwyn Ruusniel Alfons; Jouverd F. Frans; Pieter Hendra Manuputty; Rizki Muhammad Ramdhan (Universitas Kristen Indonesia Toraja, 2023)
This community outreach initiative is driven by the limited awareness among the community regarding the abundant breadfruit potential thriving in the city of Ambon, which serves as an attractive resource for supporting tourism and providing a positive economic impact on the local population. Breadfruit trees are widespread along the streets and in residents' yards, possessing significant historical value for the people of Ambon. Breadfruit has long been an integral part of Ambonese culture and traditions. Consequently, empowering the community through socialization and holistic training methods is of utmost importance. This project was conducted in the village of Latuhalat, Nusaniwe District, Ambon City, Maluku Province, and was attended by local government officials, community leaders, community groups who own breadfruit trees, as well as entrepreneurs/producers and sellers of breadfruit-based products. The project progressed smoothly and effectively, resulting in increased participant understanding and knowledge, fostering awareness about the promotion and marketing of breadfruit products, and further enhancing the community's ability to manage the local breadfruit potential in support of sustainable tourism development.